Characterization of Chloroplast Genomes From Two Salvia Medicinal Plants and Gene Transfer Among Their Mitochondrial and Chloroplast Genomes - Gao, Chengwen; Wu, Chuanhong; Zhang, Qian; Zhao, Xia; Wu, Mingxuan; Chen, Ruirui; Zhao, Yalin; Li, Zhiqiang (Frontiers in Genetics, 2020)
Salvia species have been widely used as medicinal plants and have played an important role in the treatment and recovery of individuals with COVID-19. In this study, we reported two newly identified whole chloroplast genome sequences of Salvia medicinal plants (S. yangii and S. miltiorrhiza f. alba) and compared them with those of seven other reported Salvia chloroplast genomes; these proved to be highly similar in terms of overall size, genome structure, gene content, and gene order. We identified ten mutation hotspots (trnK-rps16, atpH-atpI, psaA-ycf3, ndhC-trnV, ndhF, rpl32-trnL, ndhG-ndhI, rps15-ycf1, ycf1a, and ycf1b) as candidate DNA barcodes for Salvia. Additionally, we observed the transfer of nine large-sized chloroplast genome fragments, with a total size of 49,895 bp (accounting for 32.97% of the chloroplast genome) into the mitochondrial genome as they shared > 97% sequence similarity. Phylogenetic analyses of the whole chloroplast genome provided a high-resolution of Salvia. This study will pave the way for the identification and breeding of Salvia medicinal plants and further phylogenetic evolutionary research on them as well.